The perspectives of using hybrids between nectarine (Prunus persica (L.) Batch subsp. nectarina (Ait. Shof.) and almond (Prunus amygdalus Batsch) in selection of varietes and rootstocks - А. М. Кабар; Є. П. Шоферістов; Є. Б. Піддубцева (Plant Varieties Studying and Protection)
The perspective hybrid forms between genus Prunus persica (L.) Batch and Prunus amygdalus Batsch, having high ornamental qualities and high resistance to Sphaerotheca pannosa (L v.) var. persicae Woronich., Taphrina deformans (Berk.) Tul., Clasterosporium carpophilum (L. v) Aderh., Monilia cinerea Bonord. have been obtained for using in breeding of peach and nectarine varieties and their rootstocks.